1993
DOI: 10.1063/1.860708
|View full text |Cite
|
Sign up to set email alerts
|

Recirculating induction accelerators as drivers for heavy ion fusion*

Abstract: A two-year study of recirculating induction heavy ion accelerators as low-cost driver for inertial-fusion energy applications was recently completed. The projected cost of a 4 MJ accelerator was estimated to be about $500 M (million) and the efficiency was estimated to be 35%. The principal technology issues include energy recovery of the ramped dipole magnets, which is achieved through use of ringing inductive/capacitive circuits, and high repetition rates of the induction cell pulsers, which is accomplished … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…A recirculating induction accelerator passes the beam through each core many times, reducing the mass of cores required. [3] For a recirculator, core optimization emphasizes minimizing core energy losses more than minimizing initial cost.…”
Section: Introductionmentioning
confidence: 99%
“…A recirculating induction accelerator passes the beam through each core many times, reducing the mass of cores required. [3] For a recirculator, core optimization emphasizes minimizing core energy losses more than minimizing initial cost.…”
Section: Introductionmentioning
confidence: 99%
“…A 1991 study 1 showed that a recirculating ion beam accelerator (or recirculator) would be a promising candidate for a cost-effective driver for inertial fusion energy. Its promise is derived from the fact that the beam passes multiple times through each accelerating component.…”
Section: The Small Recirculatormentioning
confidence: 99%
“…or "recirculator," offers the prospect of reduced cost relative to a conventional linear accelerator because the accelerating and focusing elements are re-used many times per shot (7). A small recirculator is being developed at LLNL to explore the beam dynamics of a HIF driver in a scaled manne~the key dimensionless parameters that characterize the beam are similar lo those of a driver-scale ring but the physical scale is much smaller (8).…”
Section: Bending Experimentsmentioning
confidence: 99%